Optimasi Tween dan Propilen Glikol dalam Self-Nanoemulsifying Drug Delivery System VCO-Minyak Daun Kemangi - Feny Dhea Camelia; Dwi Nurahmanto; Budipratiwi Wisudiyaningsih (UPT Percetakan dan Penerbitan Universitas Jember, 2021)
Basil (Ocimum basilica) contains active compounds of essential oils that have volatile properties, so it will affect its antibacterial activity. SNEDDS was chosen as a delivery system to increase essential oil stability. The purpose of this study was to determine the effect of tween 80 concentration, propylene glycol, and their interactions in VCO on SNEDDS of basil leaf oil on response and to determine the antibacterial activity with optimum characteristics. Optimization of tween 80 and propylene glycol was conducted using the VCO oil phase with a factorial design method using design expert software 11 with the response used, namely% transmittance and emulsification time. Verification and characterization were carried out including organoleptic, pH, particle size, particle distribution, then tested for antibacterial activity. The results showed that an increase of tween 80 concentration and a decrease of propylene glycol would increase the transmittance value and decrease the emulsification time. There was no interaction effect between the two. Prediction software design expert 11 showed optimum formula with a clear yellow color appearance, the distinctive odor of basil oil, has an average pH of 6.81 ± 0.03, an average particle size of 19.7 ± 0.16 nm, a particle distribution with an average PDI average of 0.163 ± 0.05. The optimum formula with a concentration of 30 μl has activity against S. thypi with an average inhibition zone diameter of 17.21 ± 1.01 mm.